The development of an E-learning arabic courseware (EZ-Arabic) for primary school / Muhammad Aiman Zamzuri - Zamzuri, Muhammad Aiman (2025)
This project focuses on the development of an E-learning arabic courseware (EZ- Arabic) for primary school. The courseware aims to reading and learning for Arabic Year 6. The main objective is to address the current challenges in reading and provide an engaging learning experience for students and teachers. The project follows the ADDIE model to ensure effective courseware development and usability for all users. Courseware is designed to be accessible to students, teachers, facilitating interactive learning and supporting students' reading and learning. Moreover, the incorporation of Universal Design for Learning (UDL) theory principles further enhances the courseware's impact on learning outcomes. The thorough evaluation of the courseware's functionality and usability ensures a seamless learning experience for both students and teachers. Overall, the courseware's success highlights its pivotal role in fostering early literacy skills and creating an E-learning arabic courseware (EZ-Arabic) For primary sch